Structure–Activity Relationships of Glucosamine‐Derived Glycerolipids: the Role of the Anomeric Linkage, the Cationic Charge and the Glycero Moiety on the Antitumor Activity. Issue 3 (15th January 2013) - Xu, Yaozu; Ogunsina, Makanjuola; Samadder, Pranati; Arthur, Gilbert; Schweizer, Frank
Abstract The potent antitumor activity of 1‐O‐hexadecyl‐2‐O‐methyl‐3‐O‐(2′‐amino‐2′‐deoxy‐β‐D‐glucopyranosyl)‐sn‐glycerol (1) was previously shown to arise through an apoptosis‐independent pathway. Here, a systematic structure–activity study in which the effects of the anomeric linkage, the cationic charge and the glycero moiety on the antitumor activity is described. Eight analogues of 1 were synthesized, and their antitumor activity against breast (JIMT1 and BT549), pancreas (MiaPaCa2) and prostate (DU145, PC3) cancer was determined. 1‐O‐Hexadecyl‐2‐O‐methyl‐3‐O‐(2′‐amino‐2′‐deoxy‐α‐D‐glucopyranosyl)‐sn‐glycerol (2) consistently displayed the most potent activity against all five cell lines with CC50 values in the range of 6–10 μM. However, replacement of the O‐glycosidic linkage by a thioglycosidic linkage or replacement of the amino group by an azide or guanidino group leads to a threefold or greater decrease in potency. The glycero moiety also contributes to the overall activity of 1 and 2 but its effects are of lesser importance. Investigation into the mode of action of this class of compounds revealed that, in agreement with previous findings, the cytotoxic effects arise through induction of large acid vacuoles.